Unique pressure‐crystallized structures in ternary bisphenol‐a polycarbonate/dioctyl phthalate/fullerene C60 composites. Issue 3 (7th December 2012) - Tian, Jiaojiao; Liu, Guodong; Chen, Xin; Lu, Jun; Zhou, Zuowan; Huang, Rui
Abstract We report pressure‐controlled fast growth of unique crystalline structures of bisphenol‐A polycarbonate (PC) was achieved by the introduction of both dioctyl phthalate (DOP) and fullerene C60. PC/DOP/C60 ternary composites with an overall good C60 dispersion were prepared by an easy physical and mechanical route, and then crystallized in a piston‐cylinder high‐pressure apparatus by varying temperature, pressure, crystallization time and composite composition. The crystallization of PC was greatly hastened by the blending with DOP and C60, and its melting point was increased to 288.25 degrees centigrade by the subsequent high‐pressure treatment, which was around 40° centigrade higher than that of the samples crystallized at normal pressure. Three‐dimensional spiky crystalline spheres were formed with the increase of crystallization temperature, which began with zero‐dimensional nanogranules, and then developed by merging process through the stages of one‐dimensional lamellar crystallites and two‐dimensional dendrites. With pressure increased, the granules merged first into plate crystals, and then into micro‐spheres with rugged surfaces or porous structures. Also, sometimes the granules organized into rugged crystalline nanoballs, and peony‐like stereo‐open structures were observed by changing composite composition. The as‐prepared three‐dimensional crystalline structures, with their large specific areas, may diversify niche functional applications as surface active materials. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013